T cell reactivity against the SmD183–119 C terminal peptide in patients with systemic lupus erythematosus. Issue 9 (1st September 2002) - Riemekasten, G; Weiss, C; Schneider, S; Thiel, A; Bruns, A; Schumann, F; Bläss, S; Burmester, G-R; Hiepe, F
Abstract : Background: The SmD183–119 peptide is a major target of the B cell response in patients with systemic lupus erythematosus (SLE). Objective: To investigate the T cell response directed against this peptide, its disease specificity, and possible impact on SLE pathogenesis. Methods: Peripheral blood mononuclear cells derived from 28 patients with SLE and 29 healthy and disease controls were stimulated by the SmD183–119 and the recombinant (r)SmD1 protein, and [ 3 H]thymidine incorporation was measured. Patients with SLE were simultaneously tested for autoantibodies, disease activity, clinical symptoms, and medical treatments. Results: T cell reactivity against the SmD183–119 peptide was detected in 11/28 (39%) patients with SLE and against the rSmD1 protein in 10/28 (36%) patients. In contrast, only 2/29 (7%) controls exhibited SmD1 reactivity. An analysis of proliferation kinetics showed that SmD1 reactive T cells are activated in vivo, as additionally confirmed by cytometric analysis. Addition of mammalian dsDNA to rSmD1 enhanced the rSmD1-specific T cell response. SmD183–119 -specific T cell reactivity was significantly more common in patients with cardiac and pulmonary symptoms. No correlation between T and B cell responses and disease activity was seen. Conclusion: SmD183–119 is a major T cell epitope of SmD1, commonly recognised by T cells from patients with SLE and much less commonly found by healthy or disease controls. This strong T cell reactivity as well as the high frequency and specificity of anti-SmD183–119 antibodies in SLE suggest a possible role in SLE pathogenesis, at least in a subset of patients.